Cupping Therapy May be Harmful for Eczema: A PubMed Search. (27th October 2013) - Hon, Kam Lun E.; Luk, David Chi Kong; Leong, Kin Fon; Leung, Alexander K. C.
Abstract : Eczema is a common childhood atopic condition and treatment is with emollients, topical corticosteroids, and avoidance of possible triggers. S. aureus colonization is a common complication. As there is no immediate cure, many parents seek alternative therapies that claim unproven therapeutic efficacy. We report a girl with long history of treatment noncompliance. After practicing a long period of dietary avoidance and supplementation, the grandparents took her to an alternative medicine practitioner. Following cupping therapy and acupuncture, the child developed blistering and oozing over her back the next day, which rapidly evolved to two large irregular-edge deep ulcers. She was treated with intravenous antibiotics and received multidisciplinary supportive intervention. Using search words of "cupping, " "eczema, " and "atopic dermatitis, " only two reports were found on PubMed. Therapeutic efficacy was claimed but not scientifically documented in these reports. Childhood eczema is an eminently treatable atopic disease. Extreme alternative therapy seems not to be efficacious and may even be associated with serious undesirable sequelae. Physicians should be aware of various alternative treatment modalities and be prepared to offer evidence-based advice to the patients with eczema and their families.